2007
DOI: 10.1007/s00401-007-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

The dentate nucleus in Friedreich’s ataxia: the role of iron-responsive proteins

Abstract: Frataxin deWciency in Friedreich's ataxia (FRDA) causes cardiac, endocrine, and nervous system manifestations. Frataxin is a mitochondrial protein, and adequate amounts are essential for cellular iron homeostasis. The main histological lesion in the brain of FRDA patients is neuronal atrophy and a peculiar proliferation of synaptic terminals in the dentate nucleus termed grumose degeneration. This cerebellar nucleus may be especially susceptible to FRDA because it contains abundant iron. We examined total iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
139
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 30 publications
5
139
2
1
Order By: Relevance
“…Eventual degeneration of sensory axons is seen in peripheral nerves, posterior columns of the spinal cord, corticospinal tracts, and dentate nucleus of the cerebellum ensues (237,337). Immunocytochemical studies show dysregulation of ferritin, suggesting that depletion of Fpn occurs in the neuropil of the dentate nucleus (237).…”
Section: Brain Disorders Of Mitochondrial Iron Dyshomeostasismentioning
confidence: 99%
“…Eventual degeneration of sensory axons is seen in peripheral nerves, posterior columns of the spinal cord, corticospinal tracts, and dentate nucleus of the cerebellum ensues (237,337). Immunocytochemical studies show dysregulation of ferritin, suggesting that depletion of Fpn occurs in the neuropil of the dentate nucleus (237).…”
Section: Brain Disorders Of Mitochondrial Iron Dyshomeostasismentioning
confidence: 99%
“…These studies revealed a prominent neuronal expression of ferroportin in regions like the cerebral cortex, hippocampus, and cerebellum, whereas the opposite seemed to apply to regions like the striatum and thalamus (Burdo et al 2001;Koeppen et al 2007;Moos and Rosengren Nielsen 2006;Wu et al 2004). Despite the fact that these studies have provided evidence of ferroportin expression, a detailed mapping of its spatial distribution pattern would nonetheless enhance the understanding of ferroportin as an iron exporter throughout the brain.…”
Section: Introductionmentioning
confidence: 86%
“…Ferroportin was detected in discrete brain regions of the mouse (Wu et al 2004), rat (Burdo et al 2001;Moos and Rosengren Nielsen 2006), and man (Koeppen et al 2007). These studies revealed a prominent neuronal expression of ferroportin in regions like the cerebral cortex, hippocampus, and cerebellum, whereas the opposite seemed to apply to regions like the striatum and thalamus (Burdo et al 2001;Koeppen et al 2007;Moos and Rosengren Nielsen 2006;Wu et al 2004).…”
Section: Introductionmentioning
confidence: 94%
“…destruction of the dorsal root ganglia, the dorsal nuclei of Clarke, and the long spinal fiber tracts [9] . Three (not necessarily exclusive) features of DN pathology in FA have been discussed: transsynaptic neuronal atrophy [10] , increased iron content (as suggested by increased T2 * MRI relaxation rates [11] ), and/or a relative increase in iron concentration in a degenerating, increasingly compact DN with normal absolute iron levels [9] . TCS cannot ultimately decide between these different possibilities: hyperechogenicity results from the reflection of ultrasound waves at interfaces with differing acoustic impedance, and such interfaces might result from both gliosis due to atrophy and increased iron content.…”
Section: Discussionmentioning
confidence: 99%
“…DN pathology should thus be added to other early and central features of FA, i.e. destruction of the dorsal root ganglia, the dorsal nuclei of Clarke, and the long spinal fiber tracts [9] . Three (not necessarily exclusive) features of DN pathology in FA have been discussed: transsynaptic neuronal atrophy [10] , increased iron content (as suggested by increased T2 * MRI relaxation rates [11] ), and/or a relative increase in iron concentration in a degenerating, increasingly compact DN with normal absolute iron levels [9] .…”
Section: Discussionmentioning
confidence: 99%